Towards an Alternative Development Management Paradigm? - Shutt, Cathy (Rapport 2016:07, 2016)
Demonstrating results has been a concern in international development cooperation ever since it was started and in recent years there has been an increased focus on achieving and reporting on “results”. Despite the fact that everyone involved in development cooperation wants to make a difference there has been a growing criticism from practitioners about the “results agenda” based on a concern that the approaches used are not fit for purpose. In the EBA-report, Cathy Shutt, at the University of Sussex, scrutinizes the recent critical debate about results based management, and the main arguments and motives behind the criticism. She shows that the debate is not only a matter of obsessive measurement and reporting of meaningless numbers for political accountability, but also a matter of problematic assumptions and how we think about development, evidence and learning. In the report, Shutt also explores what could be learned from those who are not just critiquing results based management approaches but also proposing alternatives. Are these new alternatives an answer to the criticism?
Keywords: IMPORTANT

Navigation by Judgment: Why and when Top Down Management of Foreign Aid Doesn't Work - Honig, Dan (Oxford University Press, 2018)
Foreign aid organizations collectively spend hundreds of billions of dollars annually, with mixed results. Part of the problem in these endeavors lies in their execution. When should foreign aid organizations empower actors on the front lines of delivery to guide aid interventions, and when should distant headquarters lead? In Navigation by Judgment, Dan Honig argues that high-quality implementation of foreign aid programs often requires contextual information that cannot be seen by those in distant headquarters. Tight controls and a focus on reaching pre-set measurable targets often prevent front-line workers from using skill, local knowledge, and creativity to solve problems in ways that maximize the impact of foreign aid. Drawing on a novel database of over 14,000 discrete development projects across nine aid agencies and eight paired case studies of development projects, Honig concludes that aid agencies will often benefit from giving field agents the authority to use their own judgments to guide aid delivery. This "navigation by judgment" is particularly valuable when environments are unpredictable and when accomplishing an aid program's goals is hard to accurately measure. Highlighting a crucial obstacle for effective global aid, Navigation by Judgment shows that the management of aid projects matters for aid effectiveness.

How DFID can better manage complexity in development programming - Sharp, Samuel; Valters, Craig; Whitty, Brendan (ODI, 2019)
The United Kingdom’s (UK) Department for International Development (DFID) is an ambitious government department that is committed to reducing poverty and conflict overseas. Many of the issues on which DFID works are complex; whether focused on climate change, gender equality, health or other priorities, simple solutions rarely exist. And to tackle these complex challenges, DFID staff must interact with unpredictable systems of political, organisational and individual behaviours and incentives. There is a risk that complex problems spur more complicated programmes; that the complexity of development challenges is addressed through designing programmes with too many projects and implementers. While there may be valid reasons for this, too many of these complicated programmes will overburden staff. This briefing note is the outcome of an ongoing process within DFID to confront these issues and answer the question: how can DFID design and manage programmes to address complex development challenges without creating too much staff workload? Key messages DFID deals with complex problems, which require flexible systems to support testing, learning and adaptation. • Complex problems do not necessarily require workload-heavy delivery structures, but simpler approaches depend on delivery partners’ experience and competence. • However, programmes that tackle complex problems do require more hands-on engagement and face more workload from inflexible compliance requirements. We suggest that DFID and similar agencies: • Pay closer attention to delivery options in programme design, making use of existing options where possible and, where not, fostering local organisations through long-term investments. • Encourage programme designers to articulate how ambition matches resources and consider ‘good enough’ design. • Reduce the burden of compliance by cultivating partner autonomy, reassessing results and valuefor-money requirements and promoting more flexible contracting and procurement. • Plan and prioritise management resources across a portfolio of programmes to make sure they can be focused in the right areas, where the complexity of the problem requires greater engagement.

Politics matters, so what? Time for bigger bets (and more learning) on adaptive programming - Alan (www.globalintegrity.org, 2016)
By Alan Hudson, Executive Director, Global Integrity, July 26, 2016 Politics matters. Context too. And blueprints have limited value. Our strategy is based on these insights, so we’re totally on board. A World Development Report (WDR) that puts power and politics...

When theory meets reality: assumptions, feasibility and implications of a complexity-informed approach - Buffardi, Anne (Methods Lab, 2016)
Over the last half century, repeated calls for adaptive learning in development suggests two things: many practitioners are working in complex situations that may benefit from flexible approaches, and such approaches can be difficult to apply in practice. • Complexity thinking can offer useful recommendations on how to take advantage of distributed capacities, joint interpretation of problems and learning through experimentation in complex development programmes. • However, these recommendations rely on underlying assumptions about relationships, power and flexibility that may not hold true in practice, particularly for programmes operating in a risk averse, results-driven environment. • This paper poses guiding questions to assess the fit and feasibility of integrating complexity informed practices into development programmes.

The Politics of Evidence and Results in International Development: Playing the Game to Change the Rules? - Eyben, Rosalind; Guijt, Irene; Roche, Chris; Shutt, Cathy (Practical Action Publishing, 2015)
Understanding and demonstrating the effectiveness of efforts to improve the lives of those living in poverty is an essential part of international development practice. But who decides what counts as good or credible evidence? Can the drive to measure results do justice to and promote transformational change change that challenges the power relations that produce and reproduce inequality, injustice and the non-fulfillment of human rights? The Politics of Evidence in International Development provides a critical examination of the results agenda, with practical strategies for rendering it more helpful in supporting transformative development. The book deconstructs the origins and concepts of the results and evidence agendas employed in international development. It describes with concrete examples the current effects and consequences of the agenda, and goes on to outline a range of strategies used by individuals and organizations to resist, adapt or comply with the useful and problematic demands for results-oriented measurement and evidence of value for money."

Global governance and local peace: accountability and performance in international peacebuilding - Campbell, Susanna (Cambridge University Press, 2018)
Local peacebuilding and global accountability -- The country context--Burundi from 1999 to 2014 -- Ingos in peacebuilding--globally unaccountable, locally adaptive -- International organizations in peacebuilding--globally accountable, locally constrained -- Bilateral development donors--accountable for global targets, not local change

Managing Upward and Downward Accountability in an International Development Project - A Case Study of a World Bank Telecommunications Infrastructure Project in Benin - Kolker, Eva; Kulldorff, Catharina (Master's Thesis, Stockholm School of Economics, 2013)
Keywords: Downward accountability; Upward accountability

Is there a new Washington Consensus? An analysis of five World Development Reports - Evans, Alice (From Poverty to Power, 2017)
Is there a new Washington Consensus? Alice Evans analyses the last five World Development Reports and finds significant changes in orthodoxy, but also big gaps

Still watering white elephants? The blueprint versus process debate thirty years on - Booth, David (Perspectives on politics, production and public administration in Africa: essays in honour of Ole Therkildsen, 2015)

Learning and Results in World Bank Operations: Toward a New Learning Strategy - World Bank (IEG , The World Bank, 2015)
This report is the second in a program of evaluations that the Independent Evaluation Group (IEG) is conducting on the learning that takes place through World Bank projects. Learning and knowledge are treated as parts of a whole and are presumed to be mutually reinforcing.
Keywords: IMPORTANT

The Clash of the Counter-bureaucracy and Development - Natsios, Andrew (The Center for Global Development, 2010)
In this essay, Andrew Natsios gives a first-hand account of what he finds most hinders USAID—layers of bureaucracy that misguide and derail development work.

Evaluating Complexity. Propositions for improving practice - Preskill, Hallie; Gopal, Srik (FSG, 2014)
9 propositions can help evaluators measure progress on complex social problems.
Keywords: IMPORTANT

Release the pressure on governance practitioners - de Weijer, Frauke; Hauck, Volker (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Improving development aid design and evaluation: Plan for sailboats, not trains - Kleinfeld, Rachel (Carnegie Endowment for International Peace, 2015)
How do reforms that require political engagement differ from traditional technical reforms? Why is political engagement different, and what are the implications for design and evaluation? How should development programmes that engage politics be designed? And how can those who fund or implement such programmes evaluate whether their efforts are contributing to reform? This report …
Keywords: IMPORTANT

World Development Report 2017: Governance and the Law - World Bank (The World Bank, 2017)

From best practice to best fit: understanding and navigating wicked problems in international development - Ramalingam, Ben; Laric, Miguel; Primrose, John (Working Paper, 2014)

Navigating by Judgment: Organizational Structure, Autonomy, and Country Context in Delivering Foreign Aid - Honig, Daniel (Harvard University, Graduate School of Arts & Sciences, 2015)
This dissertation examines when initiatives by International Development Organizations (IDOs) are more, and less, successful. The core argument is that allowing field-level agents to drive initiatives – what I call organizational Navigation by Judgment – will often be the most effective way to deliver aid. This inverts what a classical application of the principal agent model – the workhorse of studies of public management and bureaucracy – would predict, with better performance resulting from less control. In the delivery of foreign aid the costs of monitoring to the principal are often overshadowed by the deleterious effects of the monitoring itself. The core of the argument is that development implementation requires soft information, tacit knowledge, and flexibility that are crowded out by tight controls or an organizational navigation strategy focused on short term measurement and targets. As a result there are increasing returns to Navigation by Judgment in environments that are uncertain or difficult to understand from the outside and tasks where outputs are difficult to observe and/or poorly correlated with long term intervention goals. Insecure political authorizing environments which constrain the autonomy of IDOs prevent these organizations from Navigating by Judgment in situations where this is the best strategy. Empirically, this dissertation examines a cross-IDO dataset of projects (including over 14,000 projects over 50 years over 9 organizations), which I have assembled. It also examines eight cases of development interventions in Liberia and South Africa. These cases are matched pairs comparing the performance and navigation strategies of the US Agency for International Development (a low autonomy IDO) and the UK’s Department for International Development (a higher autonomy IDO) in capacity building and health sector interventions.
Keywords: IMPORTANT

It's the politics! Can donors rise to the challenge? - Unsworth, Sue (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Simplexity² or: How I Learned to Stop Worrying and Love Complexity in Development - Prieto Martin, Pedr (Complexity and Development Seminar Series, 2018)
This seminar is the fifth in a series that aims to share cutting edge thinking and research being done at IDS and the University of Sussex around how we practically capture and account for complexity across a variety of sustainable development contexts. Join us for a fascinating trip from Athens to Xiaogang where, assisted by Steve Jobs, Sun Tzu and Aristotle, and with the help of a series of memorable diagrams, we attempt to alchemise development’s complexity into… a simple living tree. The seminar aims to integrate into an accessible narrative notions from various disciplines related to complexity science –including psychology, philosophy, organisational development and software engineering– as a way to articulate essential complexity concepts. Insights emerging from our cluster’s research on Adaptive Management and on the use of Frontier Technologies for development are linked with ideas presented by Prof. Chambers, Burns, Scoones and Ang in the previous seminars, to explore what complexity means in practice for development professionals and how we can discern and handle it at best. About the Speaker Pedro Prieto Martín is a software engineer turned trans-disciplinary social scientist. Pedro’s academic background includes degrees in Computer Science, Business Administration, Philosophy, and Sociology from different Spanish universities. After working for years at Hewlett-Packard in Germany as the Technical Lead of a development team, he moved to Latin America, where for years he researched the application of ICT to improve local governance and promote social change. Before joining the Digital and Technology cluster he supported and researched, at the local level, the social mobilisation processes that resulted from the “indignados” movement in Spain and their use of ICT. At IDS, Pedro has investigated the drivers of adaptiveness in accountability interventions, as part of MAVC. He now coordinates the learning component of DFID’s “Frontier Technologies Livestreaming (FTL)” programme, which has been recently awarded UK’s Civil Service Award for Innovation. FTL supports DFID country offices to experiment with the use of emerging technologies to address development challenges.